Exploring Attitudes and Readiness for EMI among Moroccan Upper Secondary School Science Teachers and Students: Rehamna Directorate as a Case Study - Yassine Elfaizi; Zahra EL Aouri (Journal of English Language Teaching and Linguistics, 2025)
This study explores Moroccan upper secondary school science teachers’ and students’ attitudes and readiness for adopting English as a Medium of Instruction (EMI). It aims to enhance understanding of the potential success and challenges of implementing this teaching approach in Moroccan science classes. Data was collected through two questionnaires targeting teachers’ and students’ attitudes, readiness, anticipated challenges, and their expectations and needs for adapting to EMI. The analysis revealed that while both groups acknowledge the critical role of English in advancing scientific research, concerns persist due to their Francophone educational background and limited English proficiency. Despite these challenges, respondents expressed positive attitudes toward EMI adoption, emphasizing that the transition should be gradual and supported by translanguaging practices and continuous training for both students and teachers. This study underscores the importance of introducing EMI in the early stages of students’ education and implementing it gradually to ensure long-term success. To overcome linguistic barriers, it recommends dedicating more time to English language learning within the curriculum. These findings contribute to understanding how EMI can be effectively integrated into Morocco’s educational system, aligning with global trends in science education and internationalization.Keywords: EMI, CLIL, translanguaging, globalization, lingua franca, internationalization